Evolution of the angiopoietin-like gene family in teleosts and their role in skin regeneration - Costa, Rita A. (2017)
Background The skin in vertebrates is a protective barrier and damage is rapidly repaired to re-establish barrier function and maintain internal homeostasis. The angiopoietin-like (ANGPTL) proteins are a family of eight secreted glycoproteins with an important role in skin repair and angiogenesis in humans. In other vertebrates their existence and role in skin remains largely unstudied. The present study characterizes for the first time the homologues of human ANGPTLs in fish and identifies the candidates that share a conserved role in skin repair using a regenerating teleost skin model over a 4-day healing period. Results Homologues of human ANGPTL1-7 were identified in fish, although ANGPTL8 was absent and a totally new family member designated angptl9 was identified in fish and other non-mammalian vertebrates. In the teleost fishes a gene family expansion occurred but all the deduced Angptl proteins retained conserved sequence and structure motifs with the human homologues. In sea bream skin angptl1b, angptl2b, angptl4a, angptl4b and angptl7 transcripts were successfully amplified and they were differentially expressed during skin regeneration. In the first 2 days of skin regeneration, re-establishment of the physical barrier and an increase in the number of blood vessels was observed. During the initial stages of skin regeneration angptl1b and angptl2b transcripts were significantly more abundant (p < 0.05) than in intact skin and angptl7 transcripts were down-regulated (p < 0.05) throughout the 4-days of skin regeneration that was studied. No difference in angptl4a and angptl4b transcript abundance was detected during regeneration or between regenerating and intact skin. Conclusions The angptl gene family has expanded in teleost genomes. In sea bream, changes in the expression of angptl1b, angptl2b and angptl7 were correlated with the main phases of skin regeneration, indicating the involvement of ANGPTL family members in skin regeneration has been conserved in the vertebrates. Exploration of the fish angptl family in skin sheds new light on the understanding of the molecular basis of skin regeneration an issue of importance for disease control in aquaculture.